Climate Change and Organic Agriculture - Khanal, Ram Chandra (Journal of Agriculture and Environment, 2009)
This paper attempts to explore some research findings focusing on the climate change impact on (organic) agriculture and agriculture impact on climate change through a literature review. This review reveals that climate change and agriculture are closely linked and interdependent. Compared to conventional agriculture, organic agriculture is reported to be more efficient and effective both in reducing GHGs (CO2, CH4 and N2O) emission mainly due to the less use of chemical fertilizers and fossil fuel. Organic agriculture also reported to be climate change resilience farming systems as it promotes the proper management of soil, water, biodiversity and local knowledge there by acting as a good options for adaptation to climate change. But, due to lack of proper research, the contribution of organic agriculture for climate change adaptation and mitigation is yet to be known in the Nepalese context. It is argued that organic agriculture positively contributes to offset negative impacts of climate change, but there is inadequate systematic data to substantiate this fact. Key words: Adaptation; Climate change; Greenhouse gases mitigation; Organic agriculture; etc. The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 116-127